THE INFLUENCE OF THE BRACELET “POWER BALANCE” NO STATIC AND DYNAMIC BALANCE OF HEALTHY INDIVIDUALS (Fiep Bulletin - online, 2012)
Postural balance refers to the alignment of the joint segments needed to keep the center of gravity within the limits of stability. Currently the is a propaganda in the media of a bracelet that has the effect of improving balance, muscle strength and range of motion. The manufacturer of the band admits that the effects are immediate and directly reacting positively in the electromagnetic field of the human body. However, the same scientific evidence is scarce. The aim of this study was to evaluate the influence of the bracelet before the Power Balance ® static and dynamic balance of healthy subjects and physically active. Thus, the groups were divided as GE (experimental group) who used strap Power Balance ®, CG (control group) not used bracelet and GCN (negative control group) who used a placebo bracelet. Regarding the results, there was no statistical difference between the tests of static and dynamic balance applied to different groups. Therefore, the Power Balance wrist showed no significant improvement over the static and dynamic balance and so little a placebo effect was observed by Power Balance bracelets and similar.
Keywords: balance; Dynamic equilibrium; Bracelet; Power Balance®